Inelastic and quasi-elastic neutron scattering spectrometers in J-PARC - Seto, H.; Itoh, S.; Yokoo, T.; Endo, H.; Nakajima, K.; Shibata, K.; Kajimoto, R.; Ohira-Kawamura, S.; Nakamura, M.; Kawakita, Y.; Nakagawa, H.; Yamada, T. (Biochimica et biophysica acta. General subjects, 2017)
J-PARC, Japan Proton Accelerator Research Complex provides short pulse proton beam at a repetition rate 25Hz and the maximum power is expected to be 1MW. Materials and Life Science Experimental Facility (MLF) has 23 neutron beam ports and 21 instruments have already been operated or under construction/commissioning. There are 6 inelastic/quasi-elastic neutron scattering spectrometers and the complementary use of these spectrometers will open new insight for life science. This article is part of a Special Issue entitled “Science for Life” Guest Editor: Dr. Austen Angell, Dr. Salvatore Magazù and Dr. Federica Migliardo. •Status of inelastic- and quasi-elastic neutron scattering spectrometers in J-PARC is shown.•Six spectrometers cover wide E–Q space and give opportunities for biology and biophysics.•Two experimental results on bio-related materials are shown as examples.